Guidelines for Mainstreaming Road Safety in Regional Trade Road Corridors - Breen, Jeanne (World Bank, Washington, DC, 2013)
The global crisis of road traffic injury is escalating in low-income and middle income countries to devastating effect; with road traffic crashes a leading cause of death. The World Health Organization (WHO) estimates that 1.24 million people were killed on the world's roads in 2010 and between 20-50 million more suffer non-fatal injuries from road traffic collisions each year. Among young people aged 15-44 years, road traffic crashes are the second leading cause of death after HIV/AIDS. The guidelines presented here are an important contribution to addressing the challenge of road safety management in regional trade corridors. Developed jointly by the Sub-Saharan Africa Transport Program (SSATP) and the World Bank, they are intended to serve as a guide for mainstreaming road safety in regional trade corridor investment programs in developing countries. The guidelines present a roadmap and set of tools with templates for terms of reference to assist in the identification, preparation and implementation of effective road safety projects in regional trade corridors, based on the lessons and global best practice experience. The publication outlines a systematic and logical process for directly addressing priority road safety needs on regional corridors in a streamlined and iterative manner, that will be relevant not only within Africa, but also to other developing regions of the world.